Kontekstualitas Modul Matakuliah Pewara pada Mahasiswa Program Studi Bahasa Indonesia - Agung Nugroho; Syaiful Abid (Jurnal KIBASP (Kajian Bahasa, Sastra dan Pengajaran), 2019)
The purpose of this research is to find out the process of developing contextual lecturer modules based on contextual students of the Indonesian language and literature education study program STKIP-PGRI Lubuklinggau. The method used by the Research & Development (R&D) model of Dick & Carey with stages, 1) analysis of needs and goals; 2) learning analysis; 3) analysis of learning (students) and context; 4) formulating performance goals; 5) developing instruments; 6) develop learning strategies; 7) developing and choosing learning materials; 8) design and conduct formative evaluations; 9) make revisions; 10) summative evaluation. The results of the study, the percentage of small group trial questionnaire of 92.78% included in the very positive category. Large group trials based on a questionnaire given to students get a very positive response with a percentage of 91.15%, the results of the test of the ability of students after using the module module 10 subjects got very good grades with a score of 8-10 the percentage of 38.46% , as many as 8 people who scored 6.6 - 7.9 with a good category and a percentage of 30.77%, the number of students who get enough grades only 4 people with a score of 6 or only 15.38%, and students who score less as many as 4 people with a range of values ​​from 4.6 to 5.5 or by 15.38%. Conclusions, the development of contextual lecturer modules based on students' contextual study programs in Indonesian language and literature education in the category of very good and practical for students to use. Keywords: Contextuality, Modules, Pewara Course.